CONTENT OF THE STRUCTURE OF MULTIMEDIA ELECTRONIC TEXTBOOKS AS A TOOL TO INCREASE EFFICIENCY IN THE EDUCATIONAL PROCESS - Valiyeva Shakhlo Akmalovna (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
This article examines the role and importance of e-textbooks in improving the quality of education. It also suggests the current shortcomings and problems, as well as the necessary steps to be taken in this regard.